Primary medical and health preparedness and people's life satisfaction in China: The mediating role of satisfaction with medical and health services - Tang, Zhiwei; Ye, Changxiu; Fu, Zhuang; Zhang, Jingran; Gong, Zepeng (Frontiers in Public Health, 2023)
Objective: To examine the association between primary medical and health preparedness (PMHP), satisfaction with medical and health services (SMHS), and life satisfaction (LS). Methods: Using the latest national representative data from the 2019 Chinese Social Survey and the 2018 Health Statistics Yearbook for each province in China, we conducted multi-level models to test the effect of three aspects of PMHP (the number of primary medical and health institutions (PMHIs), the number of beds in PMHIs, and the number of staff in PMHIs) on LS, and the mediation role of SMHS in this effect. Results: The number of staff in PMHIs has a significant positive effect on people’s LS. Besides, this effect is mediated completely by SMHS. However, the number of PMHIs and the number of beds in PMHIs do not affect LS significantly. Conclusions: PMHP has a positive impact on LS, but this impact is associated only with the number of staff in PMHIs. Therefore, governments should focus on optimizing human resources in PMHIs to meet the LS needs of individuals.